New records of Euglenophyta from Korea - Han-Soon Kim (Journal of Ecology and Environment)
The present study summarized the occurrence, distribution and autecology of 18 taxa in the class Euglenophyceae collected from several swamps, reservoir and mountain wetlands in the South Korea from 2009 to 2013. This paper deals with 18 taxa consisting of 3 taxa of Colacium Ehrenberg, 2 taxa of Phacus Dujardin, 13 taxa of Trachelomonas Ehrenberg, which are recorded for the first time in Korean freshwater algal flora.